2021
DOI: 10.3389/fimmu.2021.753044
|View full text |Cite
|
Sign up to set email alerts
|

Plasma MicroRNA Signature Panel Predicts the Immune Response After Antiretroviral Therapy in HIV-Infected Patients

Abstract: BackgroundApproximately 10–40% of people with human immunodeficiency virus (HIV) infection are unable to obtain successful improvements in immune function after antiretroviral therapy (ART). These patients are at greater risk of developing non-acquired immunodeficiency syndrome (AIDS)-related conditions, with the accompanying increased morbidity and mortality. Discovering predictive biomarkers can help to identify patients with a poor immune response earlier and provide new insights into the mechanisms of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…These five miRNAs were utilized to create a predictive algorithm that could successfully and precisely distinguish INRs from IRs to predict PIR following ART. Furthermore, miR-16-5p might prevent the growth of CD4 + T cells by regulating calcium flow ( 142 ). These prognostic miRNA biomarkers may enhance the early detection of PIR.…”
Section: Plasma Markersmentioning
confidence: 99%
“…These five miRNAs were utilized to create a predictive algorithm that could successfully and precisely distinguish INRs from IRs to predict PIR following ART. Furthermore, miR-16-5p might prevent the growth of CD4 + T cells by regulating calcium flow ( 142 ). These prognostic miRNA biomarkers may enhance the early detection of PIR.…”
Section: Plasma Markersmentioning
confidence: 99%
“… 31 In addition, miR-16-5p has been documented to predict poor immune response following antiretroviral therapy in HIV-infected patients. 32 Also, Li et al . observed that miR-16-5p was involved in the promoting effects of M1 macrophage-released exosomes on T cell-dependent immune response via PD-L1 in GC.…”
Section: Discussionmentioning
confidence: 97%
“…Approximately 10-40% of HIV-infected patients fail to achieve meaningful or sustained improvement in immune function after ART. Therefore, investigation of potential roles that miRNAs may play in immune recovery during or after antiretroviral therapy (ART) in HIV-1 patients and immunological non-responders (INRs) has already been initiated ( 17 , 19 , 80 ). miRNA sponges are RNA transcripts which include long non coding RNAs (lncRNAs) and circular RNAs (circRNAs), that associate with and sequester miRNAs, thus not allowing them to interact with their target mRNAs ( 81 ).…”
Section: Interplay Between Host Mirnas and Hiv-1mentioning
confidence: 99%
“…Past evidence has demonstrated that miRNAs are involved not only in HIV pathogenesis before treatment, but also in the immune recovery process during antiretroviral therapy (ART), and may serve as biomarkers and even as predictive markers for immune responses after initiation of ART (17)(18)(19). This review aims to summarize major advancements made in the field of miRNAs and HIV.…”
Section: Introductionmentioning
confidence: 99%